Pengaruh Persepsi Kualitas Produk, Influencer Review, Kepercayaaan Merek dan Citra Merek terhadap Minat Beli Produk Scarlett Whitening di Kota Purwokerto - Lynda Putri Pravitasari; Tri Esti Masita; Cahyaningtyas Ria Uripi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Recently, skin care products have become increasingly diverse, with various brands and types of products available. This research aims to examine the influence of product quality perceptions, influencer reviews, brand trust, and brand image on purchasing interest in Scarlett Whitening products in the city of Purwokerto. This research was conducted in the city of Purwokerto involving 120 respondents. Sample collection was carried out using an incidental sampling technique. Data was collected through distributing questionnaires. By using multiple linear regression analysis tools. The results of this research show that perceived product quality has a positive and significant effect on purchasing interest. Influencer reviews have a positive and significant effect on purchasing interest. Brand trust has a positive and significant effect on purchasing interest. Meanwhile, brand image has a negative and significant effect on interest in purchasing Scarlett Whitening products in the city of Purwokerto.